Respuesta :
j + t = 30
j = 2t - 3
now we sub
(2t - 3) + t = 30
3t - 3 = 30
3t = 30 + 3
3t = 33
t = 33/3
t = 11 <== Tritt's age
j = 2t - 3
j = 2(11) - 3
j = 22 - 3
j = 19 <== Jan's age
j = 2t - 3
now we sub
(2t - 3) + t = 30
3t - 3 = 30
3t = 30 + 3
3t = 33
t = 33/3
t = 11 <== Tritt's age
j = 2t - 3
j = 2(11) - 3
j = 22 - 3
j = 19 <== Jan's age
2x-3+x=30
3x-3=30
3x=33
Tritts age=x=11
Jans age=2x-3=2(11)-3=22-3=19
Tritt=11
Jan=19
3x-3=30
3x=33
Tritts age=x=11
Jans age=2x-3=2(11)-3=22-3=19
Tritt=11
Jan=19